Fundamentals of biochemistry : - Voet, Donald (John Wiley & Sons, 2006)
This text uses a more brief and qualitative approach to present biochemistry with chemical rigor, focusing on the structures of biomolecules, chemical mechanisms, and evolutionary relationships. It is written to impart a sense of intellectual history of biochemistry, an understanding of the tools and approaches used to solve biochemical puzzles, and a hint of the excitement that accompanies new discoveries.